Предмет: Алгебра,
автор: Аноним
упростите выражение
17.1
1) (х⁸ - 2) (х⁴ - 1) - х¹² + 2х⁴
2) а⁹ - 9а⁵ - (а⁴ - 9) (а⁵ + 3)
3) (х¹⁵ + 5) (х³ + 2) - 10 - х¹⁸
4) а¹² - 14а⁷ - а⁶ - 14) ( а⁷ - 1)
Срочно
tamarabernukho:
в 4) в условии все верно?
Ответы
Автор ответа:
67
Ответ:
Объяснение:
17.1
1) (х⁸ - 2) (х⁴ - 1) - х¹² + 2х⁴ =x¹²- 2x⁴- x⁸+2 - х¹² + 2х⁴ =2 - x⁸
2) а⁹ - 9а⁵ - (а⁴ - 9) (а⁵ + 3) =а⁹ - 9а⁵ - a⁹ + 9a⁵ - 3a⁴ + 27=27 - 3a⁴
3) (х¹⁵ + 5) (х³ + 2) - 10 - х¹⁸ =x¹⁸ + 5x³ + 2x¹⁵ + 10 -10- x¹⁸=2x¹⁵ +5x³
4)( а¹² - 14а⁷ - а⁶ - 14) ( а⁷ - 1)=a¹⁹ - 14a¹⁴ - a¹³ -14a⁷ - a¹² + 14а⁷ + а⁶ + 14=
=a¹⁹ -14a¹⁴ - a¹³ - a¹² + a⁶ +14
Похожие вопросы
Предмет: Русский язык,
автор: nastyakabancov
Предмет: Русский язык,
автор: 89173635446
Предмет: Русский язык,
автор: gaechka2011
Предмет: Математика,
автор: olgauazine
Предмет: Алгебра,
автор: ДЕПУЛ